Brazilian mineral clay as support for metallocene catalyst in the synthesis of polyethylene - Marques, Maria; Tiosso, Rodrigo (Publishing House of Lviv Polytechnic National University, 2010)
Silica was compared with clays as supports for metallocene. Ethylene homopolymerization with both homogeneous and heterogeneous catalysts was performed. Activation energy was higher for (n-BuCp)2ZrCl2/SiO2/MAO, although high activities were obtained for catalysts with clay. They showed Ea close to that of homogeneous precursor. Catalyst/clay control polymer morphology until 363 K. Проведено порівняння кремнезему і глини як носіїв для металоцену. З використанням гомогенних і гетерогенних каталізаторів вивчено гомополімеризаціюетилену. Встановлено, що енергія активації єв ищою для (n-BuCp)2ZrCl2/SiO2/MAO, незважаючи на те, що каталізатори на основі глини мають більшу активність. Показано, що значення енергії активації є близькими для обох випадків. Співвідношення каталізатор/глина регулює морфологію полімеру до 363 К.
Бразилійська мінеральна глина як носій металоценового каталізатора при синтезі поліетилену
Keywords: clay; support; metallocene catalysts; polyethylene; nanocomposite; глина; носій; металоценовий каталізатор; поліетилен; нанокомпозит